PENINGKATAN KEMAMPUAN MENULIS TEKS EKSPLANASI MENGGUNAKAN MODEL PEMBELAJARAN KUMON SISWA KELAS X SMK SINAR HUSNI - Bobby Pratama Putra (Universitas Negeri Medan, 2019)
Abstract This study aims to improve the ability to write explanation texts in class X SMK Sinar Husni using a kumon learning model of 32 students. This research uses a classroom action research approach. Data collection techniques in this study used test techniques. The results of the test data were analyzed by looking at the average value of the increase in pre-action, cycle I, and cycle II. Data analysis technique is done by adding up scores from assessment indicators obtained by students. In the pre-action activities the average value of students was 71.71% with completeness of 34.38% with the number of students as many as 11 people and as many as 21 people who did not complete. The first cycle of action, the average value of students 75.53 and completeness only reached 71.88% with the total number of students as many as 23 people and not as many as 9 people. While in cycle II the average value reached 80.93 with 30 students completing as many students and not completing 2 people, meaning that from cycle I to cycle II increased by 21.87%. increased. Keywords: Explanation Text, Learning, Kumon.